Buckling and free vibration analysis of bio-inspired laminated sandwich plates with helicoidal/Bouligand face sheets containing softcore. (15th February 2023) - Garg, Aman; Belarbi, M.O.; Chalak, H.D.; Li, L.; Sharma, Anshu; Avcar, Mehmet; Sharma, Neha; Paruthi, Sagar; Gulia, Reeta
Abstract: Helicoidal laminates inspired by mantis shrimp crustacean can sustain higher loads compared to conventional laminated structures. However, there is still a lack of bending studies on the plates inspired by these helicoidal structures. The buckling and free vibration studies have been undertaken in the present work on the laminated composite and sandwich plates inspired by the helicoidal structures of the biological characters. Investigations are carried out using higher-order zigzag theory. For sandwich plates, the top and bottom face sheets are assumed to be made up of helicoidal layup schemes. Different kinds of helicoidal schemes, namely, recursive, exponential, semicircular, Fibonacci, and linear helicoidal are considered during the analysis. The buckling and free vibration behavior of helicoidal-based laminated sandwich plates are compared with the conventional laminated sandwich plates such as uniform distribution and cross-ply configurations. The influence of the number of layers, helicoidal schemes, geometric properties, and end conditions on the buckling and free vibration analysis of bio-inspired helicoidal laminated composite and sandwich plates is carried out in detail. Highlights: Free vibration and buckling analysis of helicoidal laminated sandwich plates is carried out. The kinematics for the model is set within the framework of the higher-order zigzag theory. The analysis has been carried out for normal and skew plates. Hamilton's principle and the principle of minimum potential energy are used for solving free vibration and buckling problems. The model can be used to analyze and design naval, civil, automobile, and aerospace structures, domes, and pressure vessels.